Answer:
see explanation
Explanation:
To evaluate f(- x) substitute x = - x into f(x)
f(- x) = (- x)² = x² = f(x) ← circle this one
f(- x) = (- x)³ = - x³ ≠ f(x)
f(- x) = sin(- x) = - sinx ≠ f(x)
f(- x) = cos(- x) = cosx = f(x) ← circle this one
circle 1st and last function.
f(x)=x²
replace x by -x
f(-x)=(-x)²
f(-x)=x²
hence f(x)=f(-x)=x² hence circle this one.
Now f(x)=x³
replace x by -x,we get
f(-x)=(-x)³
f(-x)=-x³≠f(x)
Now, f(x)=sinx
f(-x)=sin(-x)=-sinx
f(x)≠f(-x)
Now,f(x)=cosx
f(-x)=cos(-x)=cosx=f(x)
so,f(x)=f(-x). Also circle this one.
5.3m questions
6.8m answers